2020
DOI: 10.3390/ijms22010371
|View full text |Cite
|
Sign up to set email alerts
|

MMP1 and MMP11 Expression in Peripheral Blood Mononuclear Cells upon Their Interaction with Breast Cancer Cells and Fibroblasts

Abstract: Tumor-infiltrating immune cells phenotype is associated with tumor progression. However, little is known about the phenotype of the peripheral blood mononuclear cells (PBMC) from breast cancer patients. We investigated MMP1 and MMP11 expression in PBMC from breast cancer patients and we analyzed gene expression changes upon their interaction with cancer cells and cancer-associated fibroblasts (CAF). We measured the impact of PBMC on proinflammatory gene expression in breast cancer cells, normal fibroblast (NF)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Our results showed that MMP1 and FSTL3 were significantly upregulated in LSCC and positively correlated with worse survival as well as several immune cells' infiltrations. MMP1 greatly promotes tumor cells' migration and invasion and has been reported to correlate with immune cells' infiltrations in breast and cervical cancer [ 26 , 27 ]. Eiro et al [ 28 ] found that MMP1 mediated the interaction among peripheral blood mononuclear cells, cancer cells, and cancer-associated fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that MMP1 and FSTL3 were significantly upregulated in LSCC and positively correlated with worse survival as well as several immune cells' infiltrations. MMP1 greatly promotes tumor cells' migration and invasion and has been reported to correlate with immune cells' infiltrations in breast and cervical cancer [ 26 , 27 ]. Eiro et al [ 28 ] found that MMP1 mediated the interaction among peripheral blood mononuclear cells, cancer cells, and cancer-associated fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma levels of several miRNAs, such as miR-218, miR-223, miR-7, miR30, and miR-21, were studied in hepatocellular carcinoma and gastric and ovarian cancer (62)(63)(64). Recently, the relative expressions of matrix metalloproteinases (MMPs) in blood of breast cancer patients were investigated to determine their role in cancer progression (65), hence indicating their possible application in disease prognosis. The current study also evaluated the mRNA expression of these molecules in blood of cervical cancer patients and provided a foundation for conducting an in-depth, proteomelevel analysis in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Natural compounds draw increasing interest because of their anticancer effects at the molecular level. Kaempferol is a kind of flavonoid, which widely exists in a variety of natural foods and drugs [ 22 ]. MMPs is a family of calcium, zinc, and other metal ion-dependent endopeptidases, of which MMP1, 2, and 9 are three important members [ 23 ].…”
Section: Discussionmentioning
confidence: 99%